Outcome measures reported in abstracts of randomized controlled trials in leading clinical journals: A bibliometric study - Takeshi Seta; Yoshimitsu Takahashi; Yukitaka Yamashita; Masahiro Hiraoka; Takeo Nakayama (Journal of General and Family Medicine, 2020)
Abstract Backgrounds The CONSORT for Abstracts checklist published in 2008 recommends that authors report effect size for their studies. Meanwhile, the FDA strongly recommends reporting both ratio and difference measures. However, the measures of effect used in recent clinical trial reports remain unknown. This study is aimed to reveal trends regarding the measures of effect of interventions described in abstracts of recent randomized controlled trials (RCTs) in leading journals. Methods A bibliometric analysis of data was obtained by electronic searches. Human RCTs published in 2016 in the following five journals were searched using PubMed: Annals of Internal Medicine, British Medical Journal, Journal of American Medical Association, The Lancet, and New England Journal of Medicine. Main outcome is numbers of studies reporting each measure in their abstracts. Results Among abstracts of 334 articles, measures most frequently used were relative risk alone (n = 169), followed by absolute risk alone (n = 92), and raw data alone (n = 58). Reporting of the following measures was relatively limited: both ratio and difference measures (n = 8), raw data with ratio measures (n = 5), and raw data with difference measures (n = 2). None of the studies reported raw data with both ratio and difference measures. Only 15 articles described multiple measures of effect in their abstracts. Conclusions More than half of the RCT abstracts published in the five leading journals in 2016 reported risk ratio alone to indicate effect size. Even abstracts in the five leading journals did not adhere fully to the CONSORT for Abstracts or FDA recommendations.